STUDY LITERATURE: STRATEGI PENGEMBANGAN WIRAUSAHA KECIL MENENGAH MASYARAKAT DESA DAN BISNIS YANG TANGGUH UNTUK MENGHADAPI ERA SOCIETY 5.0 - Nur, Dewi Rosidawati; Gultom, Theodora; Dewi, Intan Indria; Maliki, Budi Ilham (Gapenas Publisher, 2023)
Entrepreneurship is the endeavor of an individual to create innovative ideas to generate a product/service that can enhance the value addition of the product/service through new and different approaches, as well as being able to establish and institutionalize their business and enterprise. To avoid failure in entrepreneurship, a fairly good strategy is needed so that the endeavor can be considered independent and successful, provided that one possesses knowledge and insight into entrepreneurship. Entrepreneurial strategy is an effort to provide opportunities and chances for an entrepreneur to effectively run their business and enterprise. This research aims to identify strategies to face the Society 5.0 Era that can be utilized in developing small businesses in rural areas and making existing businesses more resilient. This study employs a qualitative descriptive method using references from various literature and journals